2021
DOI: 10.1080/07853890.2021.1962965
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic colitis: controversies in clinical symptoms and autoimmune comorbidities

Abstract: Background: Microscopic colitides are chronic immune-inflammatory bowel diseases. The typical presentation is chronic, watery diarrhoea. Inflammation mostly cannot be visualized via macroscopic inspection. The diagnosis thus requires histologic sampling. The clinical picture can vary. New investigations can prove valuable in setting up recommendations. Patients: A total of 103 patients with microscopic colitis (MC) [28 lymphocytic colitis (LC) 27.2%, 75 collagenous colitis (CC) 72.8%] in the Clinical Centre of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Our paper is an extension of two of our earlier datasets of patients with microscopic colitis (MC—103 patients) and inflammatory bowel disease (IBD—508 patients) [ 11 , 12 ]. In total, we included 611 patients in the current paper, within four groups.…”
Section: Methodsmentioning
confidence: 99%
“…Our paper is an extension of two of our earlier datasets of patients with microscopic colitis (MC—103 patients) and inflammatory bowel disease (IBD—508 patients) [ 11 , 12 ]. In total, we included 611 patients in the current paper, within four groups.…”
Section: Methodsmentioning
confidence: 99%
“…The patients completed a shortened version of the Rome III questionnaire, including only IBS symptoms [23]. Patients who fulfilled the criteria for Rome III were classified as also suffering from IBS-like symptoms since their diagnosis was MC, and thus, it cannot be called IBS [6].…”
Section: Rome III Criteriamentioning
confidence: 99%
“…The association was higher in younger patients aged 18–49 compared to older patients aged 50–59. Another retrospective study review of 103 patients with microscopic colitis reported that 40 (39%) of patients had an underlying autoimmune disease with no difference between patients with collagenous colitis and lymphocytic colitis [ 34 ]. Hashimoto thyroiditis was the most prevalent autoimmune disease in fourteen patients (35%), followed by rheumatoid arthritis in seven (17.5%), and Sjogren’s syndrome in seven (17.5%).…”
Section: Pathogenesis Of Microscopic Colitismentioning
confidence: 99%